Creating a maritime wireless mesh infrastructure for real-time applications - Lambrinos, Lambros; Djouvas, Constantinos (My University, 2011)
Advances in computing and networking technologies have revolutionised the way people communicate using interactive real-time applications such as instant messaging and audio and videoconferencing. This category of applications is nowadays readily available to users in terrestrial areas with high speed Internet connectivity. The aim of this work is to investigate the provision of IP-based network connectivity onboard sailing vessels in order to support real-time communication applications. More precisely, instead of the expensive and high-latency satellite communications solutions widely deployed in the maritime industry, we propose the use of long-range wireless networking technologies for creating a vessel-to-shore mesh network that can be used to form an infrastructure for the provision of telephony services based on Voice-over-IP (VoIP).
Keywords: Instant messaging; Internet telephony; Videoconferencing